Scaling Out Climate-Smart Agriculture for Resilient Farming in Beed district of Maharashtra - Indian Council of Agricultural Research; Natural Resource Management Division; International Water Management Institute; CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Climate-smart agriculture (CSA) is an important approach towards minimizing impacts due to climate risks and maintaining agricultural growth. This report aims to contribute towards building a national strategy for scaling out climate resilient agricultural practices and technologies by synthesizing cumulative knowledge, experiences, and learnings gained by ICAR, CCAFS, and CG Centre’s Programs in climate risk management. The report presents district level adaptation plan for resilient farming in the Beed district of Maharashtra. The process consisted of characterization of climatic risks followed by identification and prioritization of CSA technologies and practices and identifying scaling up opportunities through the convergence of government policies and programs. Drought, heat wave, dry spells, and deficit rainfall are frequently occurring climate risks in the district with severe impact on rainfed cropping system. For the identification and prioritization of CSA technologies, all potential technologies are first categorized into six main categories of water-smart, energy-smart, nutrient smart, carbon-smart, weather-smart and knowledge-smart. Thereafter, district specific suitable CSA technologies are identified following a participatory approach through stakeholder’s workshop. The identified technologies are evaluated and prioritized for implementation feasibility, acceptability, adoption barriers, synergy with government plans, incentive mechanisms and key institutions. Total estimate budget of Rs. 387.0 Crore will be required for implementing these technologies in the district. The convergence of resources from relevant government schemes/projects for mobilizing funds for prioritized CSA technologies has been proposed. The process and results provided here are intended to assist decision makers to prioritize investments for CSA interventions to build resilient farming in the district.